Back Cover: Plasma Process. Polym. 6∕2015. Issue 6 (18th June 2015) - Hur, Min; Lee, Jae Ok; Kang, Woo Seok; Song, Young‐Hoon
<x xml:space="preserve">Abstract</x> Back Cover: Feasibility tests of abating and stabilizing pollutants emitted during semiconductor manufacturing were performed by using a plasma reactor placed before a vacuum pump. TEMAZ was fully destroyed, and the destroyed TEMAZ was transformed into ZrOx particles with sub 10 nm size. Detailed abatement characteristics of N2O, CF4, CHF3, NF3, C3H6, and TEMAZ can be found in the article by Min Hur et al. on page 583.